Nonspecific neck pain - El-Allawy, Ahmad; Hecht, Nils; Luedtke, Kerstin; Schleicher, Philipp; Weidner, Norbert; Kotter, Thomas (Deutsches Ärzteblatt, 2025)
Background: Nearly half of the adults in Germany have neck pain at least once a year. Neck pain is distressing to those who suffer from it and costly to society at large. Its treatment requires a coordinated approach with the participation of general practitioners, physician specialists, and other health care professionals, such as physical therapists. The German Society for General Medicine and Family Medicine has now issued an upgraded (S1 to S3 level) set of recommendations for rational diagnosis and treatment. Methods: The new recommendations were developed in an interdisciplinary and interprofessional collaboration as specified by the rules of the Association of the Scientific Medical Societies in Germany (AWMF). Systematic searches for scientific evidence were conducted in Medline (latest update, 11/2024), and the recommendations were formulated in a structured consensus process. The guideline was practically tested in physiotherapeutic and general medical practice settings. Results: The diagnostic evaluation begins with meticulous medical history-taking and physical examination. In cases of acute neck pain (0-3 weeks) without any evidence of a structural cause (e.g., motor deficit, night pain, precipitating trauma), diagnostic imaging should generally not be per-formed. Activating therapeutic measures with a focus on self-management have shown high effect sizes (up to d >1.0). The success of such measures may depend on patient education (moderate effect size, d = 0.73). For chronic neck pain (longer than 12 weeks), exercise therapy is recommended as well. Analgesic drugs may yield short-term relief (low effect size). Conclusion: In patients with neck pain for which the medical history and physical examination do not point to a structural cause, activation is recommended as the central element of treatment.
Gesehen am 05.12.2025